2011
DOI: 10.1016/j.ygeno.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The full-length transcripts and promoter analysis of intergenic microRNAs in Drosophila melanogaster

Abstract: MicroRNA (miRNA) transcription is still not well understood until now. To increase the miRNA abundance, we stimulated miRNA transcription with CuSO(4) and knocked down Drosha enzyme using dsRNA in Drosophila S2 cells. The full length transcripts of bantam, miR-276a and miR-277, the 5'-end of miR-8, the 3'-end of miR-2b and miR-10 were obtained. We also conducted a series of miRNA promoter analysis to prove the reliability of RACE results. Luciferase-reporter assays proved that both bantam and miR-276a promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Importantly, the dual firefly/Renilla luciferase reporter system allows internal normalization of LUC expression. For example, using site-directed mutagenesis and dual LUC assays, Qian et al (2011) identified TFBSs in the promoters of the Drosophila intergenic miRNAs bantam and miR-276a. Promoter bashing in combination with sensitive reporter systems is still a powerful tool for dissecting functional regions and for empirically determining or confirming predicted TFBSs in miRNA or PCG promoters, but mutagenesis can be laborious and timeconsuming in plants, particularly due to the necessity of obtaining transgenics.…”
Section: Techniques That Bash Promoter Bashing: Tf Binding Validationmentioning
confidence: 99%
“…Importantly, the dual firefly/Renilla luciferase reporter system allows internal normalization of LUC expression. For example, using site-directed mutagenesis and dual LUC assays, Qian et al (2011) identified TFBSs in the promoters of the Drosophila intergenic miRNAs bantam and miR-276a. Promoter bashing in combination with sensitive reporter systems is still a powerful tool for dissecting functional regions and for empirically determining or confirming predicted TFBSs in miRNA or PCG promoters, but mutagenesis can be laborious and timeconsuming in plants, particularly due to the necessity of obtaining transgenics.…”
Section: Techniques That Bash Promoter Bashing: Tf Binding Validationmentioning
confidence: 99%
“…Sokol and Ambros (2005) showed that the muscle-specific transcription factors Twist (Twi) and Mef2 are key activators of miR-1 in Drosophila. Genomic studies have also identified regulators of miRNAs, such as Dorsal (Dl), c-Myc (Diminutive -FlyBase) and Ecdysone (Zeitlinger et al, 2007;Qian et al, 2011;Sempere et al, 2003). However, for many miRNAs, particularly those differentially expressed across developmental stages, the regulatory networks that control their transcription remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MiRs were first discovered in the nematode Caenorhabditis elegans by Rosalind C. Lee in 1993 [ 2 ]. Since then, abundant miRs were found in many species such as plants, animals and human being [ 3 , 4 , 5 ], and regarded as a class of highly conserved RNA in the course of evolution. So far, more than 1000 miRs are predicted in human genome, and regulate about 30% of human genes [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%